Pengaruh Microteaching Terhadap Peningkatan Keterampilan Komunikasi Guru - Regina Sipayung; Meikardo Samuel Prayuda; Margaretha Ayu Lumban Gaol; Agnes Romayani Simarmata; Ria Rasani Tumangger; Masli Tamba; Betty Agatha Sihombing (Journal on Education, 2024)
Microteaching is an innovative method that focuses on developing teaching skills on a micro scale. Research shows that the use of microteaching has a significant positive impact on improving teacher communication skills. Microteaching helps teachers improve their ability to communicate well, clearly and effectively with students through a focused and measurable teaching approach. Research conducted shows that micro teaching courses play an important role in developing teacher communication skills in the classroom. Microteaching provides teachers with the opportunity to train and improve their communication style so they can better communicate subject matter in a way that students can understand. Additionally, research shows that when teachers use microteaching to add variety to their lessons, students' active learning can increase. This confirms that microteaching can not only influence teachers' communication skills, but also create a more interactive and interesting learning environment for students. It can be concluded that microteaching has a significant positive impact on improving teacher communication skills. Through a focused and measurable approach, microteaching helps teachers improve their communication styles, increase interactions with students, and create a more effective learning environment.